Analisis Layanan Investree Peer To Peer Lending Syariah Dan Progresnya Dalam Memberikan Pinjaman Kepada Nasabah - Holilur Rahman; Istifadzah (CV. ITTC INDONESIA, 2022)
There are now fintech services in peer to peer lending that apply sharia principles in their operations. Investree has applied sharia principles to this type of financing. This study aims to analyze how sharia investree peer to peer lending service and their progress in providing loans to customers. The method used in this research is descriptive qualitative mwthod. And the results of this study show that; (1) There are two sharia-based peer to peer lending financing service provided by the Investree marketplace, namely invoice financing and online seller financing. (2) There are several factors that affect the feasibility analysis of prospective customers/borrowers to be able to enjoy Sharia-based peer to peer lending services in the Investree marketplace through the 5C plus 1S analysis instruments, namely Character factors, Capacity factors, Capital factors, Collateral factors, Condition factors, and Sharia factors.